2020
DOI: 10.1155/2020/7575862
|View full text |Cite
|
Sign up to set email alerts
|

Coexpression Network Analysis of Genes Related to the Characteristics of Tumor Stemness in Triple-Negative Breast Cancer

Abstract: Cancer stem cells (CSCs) are subsets of cells with the ability of self-renewal and differentiation in neoplasm, which are considered to be related to tumor heterogeneity. It has been reported that CSCs act on tumorigenesis and tumor biology of triple-negative breast cancer (TNBC). However, the key genes that cause TNBC showing stem cell characteristics are still unclear. We combined the RNA sequencing (RNA-seq) data from The Cancer Genome Atlas (TCGA) database and mRNA expression-based stemness index (mRNAsi) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 39 publications
3
20
0
Order By: Relevance
“…Functional analysis showed that these 111 genomic instability-related genes were enriched in the pathways associated with mitotic process. Dysregulation of mitotic processes can impact DNA replication involving mitotic nuclear division, nuclear division, and organelle fission, contributing to genome instability and OS of TNBC ( Chen L. et al, 2018 ; Si et al, 2020 ; Suo et al, 2020 ). For example, the feedback loop between Drp1-mediated mitochondrial fission and Notch signaling pathway can promote TNBC cell survival via increasing survivin expression ( Chen L. et al, 2018 ), and silibinin-induced mitochondrial fission can cause mitophagy preventing silibinin-induced apoptosis in TNBC ( Si et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Functional analysis showed that these 111 genomic instability-related genes were enriched in the pathways associated with mitotic process. Dysregulation of mitotic processes can impact DNA replication involving mitotic nuclear division, nuclear division, and organelle fission, contributing to genome instability and OS of TNBC ( Chen L. et al, 2018 ; Si et al, 2020 ; Suo et al, 2020 ). For example, the feedback loop between Drp1-mediated mitochondrial fission and Notch signaling pathway can promote TNBC cell survival via increasing survivin expression ( Chen L. et al, 2018 ), and silibinin-induced mitochondrial fission can cause mitophagy preventing silibinin-induced apoptosis in TNBC ( Si et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…By applying another network-based approach, named weighted gene co-expression network analysis (WGCNA), other studies analyzed TCGA TNBC dataset and investigated the correlation between TNBC expression and stemness, survival, and metastasis [36,37]. In particular, the authors in [36] identified a set of relevant genes, including BIRC5, CDC25A, KIF18B, KIF2C, RAD54L, and TPX2, which play important roles in the maintenance of TNBC stemness. Interestingly, we found them as switch genes in TNBC tumors vs controls, supporting the reliability of SWIM analysis.…”
Section: Identification and Characterization Of Switch Genes Associated With Tnbcmentioning
confidence: 99%
“…Previous study showned that ORC1L was up-regulated in gliomas and promoted proliferation, migration and invasion of glioma cells through activation of ERK/JNK signaling pathway 10 . In lung cancer and triple-negative BC, ORC1L was considered as a pivotal gene for the maintenance of tumor stem cell, and its expression in lung cancer was positively correlated with tumor stage 19,20 . ORC5L and ORC6L had prognostic value in hepatocellular carcinoma 17 .…”
Section: Discussionmentioning
confidence: 99%
“…ORCs are also differentially expressed in a number of tumors, such as gliomas 10 , endometrial cancer 11 , colon cancer [12][13][14] , gastric cancer 15,16 , liver cancer 17 , esophageal cancer 18 , and lung cancer 19 . They are implicated in diverse biological processes, including cell proliferation, migration, invasion, tumor stem cell maintenance, and chemotherapy resistance [11][12][13][19][20][21][22] . ORC1L, ORC5L and ORC6L have prognostic value in gastric cancer, liver cancer and colorectal cancer [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%